PENGARUH PEMBERIAN BERBAGAI KONSENTRASI MOL REBUNG BAMBU DAN PENJARANGAN BUAH TERHADAP PERTUMBUHAN DAN HASIL TANAMAN LABU MADU (Cucurbita moschata Durchesne) - Yunita Istiqomah; Eliyanti Eliyanti; Novalina Novalina (Universitas Batanghari, 2021)
The obstacle faced when cultivating honey pumpkins (Cucurbita moschata Durchesne) is that the fruit size is not uniform and even tends to get smaller so that the results are not satisfactory and are not accepted in the market. This study aims to examine the effect of the combined application of the MOL of bamboo concentration with fruit thinning on the growth and production of honey pumpkins, which was carried out from May to September 2020 in PT. Pupuk Sriwijaya land, H. Agus Salim street No. 1 Handil Jaya Village, Jelutung District, Jambi. This study used a factorial randomized block design with 2 factors, the first factor being the provision of MOL of bamboo which consisted of 4 levels of concentration, namely; without presenting the MOL of bamboo (b0), MOL of bamboo 20 ml L-1 (b1), 40 ml L-1 (b2), and 60 ml L-1 (b3). The second factor is fruit thinning, consisting of 3 levels, namely; without fruit thinning (p0), fruit thinning to 4 pieces (p1), and fruit thinning to 6 pieces (p2) with 3 replications. The results showed that the combination of concentration MOL of bamboo of 40 ml L-1 and fruit thinning to 4 pieces resulted in higher plant growth yields and greater fruit weight. This study showed that these two factors were involved in the growth and yield of honey pumpkins.